The impact of US assimilation and allotment policy on American Indian mortality - Grant Miller; Jack Shane; C. Matthew Snipp (Proceedings of the National Academy of Sciences, 2025)
In contrast to earlier US policies of open war, forcible removal, and relocation to address the “Indian Problem,” the Dawes Act of 1887 focused on assimilation and land severalty—making American Indians citizens of the United States with individually titled plots of land rather than members of collective tribes with communal land. Considerable scholarship shows that the consequences of the policy differed substantially from its stated goals, and by the time of its repeal in 1934, American Indians had lost two-thirds of all native land held in 1887 (86 million acres)—and nearly two-thirds of American Indians had become landless or unable to meet subsistence needs. Complementing rich qualitative history, this paper provides quantitative evidence on the demographic impact of the Dawes Act on mortality among American Indian children and adults. Using 1900 and 1910 US population census data to study both household and tribe-level variation in allotment timing, we find that assimilation and allotment policy increased the American Indian child mortality ratio by a little more than 15%. In secondary analyses (requiring additional assumptions) focused on total mortality, we find increases among young American Indians of nearly one-third (implying a decline in life expectancy at birth of about 20%). These results confirm contemporary critics’ adamant concerns about the Dawes Act.